Family involvement in early education and child care - Sutterby, John A., 1966- (Advances in early education and day care ;, 2016)
This being the 20th volume in the series of Advances in Early Education in Day Care, it encourages reflection on previous volumes. Family involvement has been an issue in early education going back to Pestalozzi almost two centuries ago. Although the issue has been discussed in many different ways since then, there are still areas where we have much to learn. This series approached this topic in 1998 with the publication of volume 9 edited by Stuart Reifel, Carl Dunst and Mark Wolery. What advances in the area of family involvement in early education have been made since the publication of the previous volume.